„European“ vs. „Traditional“ Values in the Bulgarian Media - Kovacheva, Ralitsa (Media and Language, 2021)
The study presented deals with the issue of the media representation of the concepts of „European values“ and „traditional Bulgarian values“ during the European election campaign in 2019. The results show that a broad misrepresentation of the European values prevails in the political discourse, based on which they are opposed to the Bulgarian values. As a result, a negative attitude towards the EU is constructed.